Potential applications of rubber buffing dust and recovered crumb rubber in cement concrete - Jurgita Malaiškienė; Tomas Astrauskas; Tomas Januševičius; Olga Kizinievič; Viktor Kizinievič (Results in Engineering)
Abstract.: Rubber waste is an important and growing part of waste. Despite variation by country due to socioeconomic factors and waste management, the rubber content remains high. The construction industry, with its large material needs, provides a promising opportunity for rubber reuse. Incorporating rubber into concrete is beneficial as a result of concrete's widespread use and long service life, keeping rubber waste out of the waste stream for extended periods. This study analyses the possibilities of using two types of waste rubber particles (rubber buffing dust (RBD), generated during the buffing of tyre treads as part of the process to restore worn tyre rubber and recovered crumb rubber (RCR), derived from the end-of-life synthetic turf containing a mixture of styrene-butadiene rubber and ethylene propylene diene monomer granules) in concrete. This waste was used to replace 5 % and 10 % of natural fine aggregate and the properties of modified concrete, such as density, flexural and compressive strength, water absorption, resistance to freezing-thawing cycles, sound absorption, and changes in structure, were analysed. The density, flexural strength, and compressive strength of the modified concrete decreased; however, the compressive strength of the concrete modified with RCR met the requirements for the Class C30/37 concrete commonly used for various structural elements, the RBD-modified concrete complied only with the Class C16/20 requirements. Water absorption in RBD concrete increased by about 60 % compared to the control sample, while capillary absorption nearly doubled due to increased open porosity. This concrete did not withstand 50 freeze-thaw cycles. RCR-modified concrete had lower water absorption, less structural inhomogeneity, withstands >100 freeze-thaw cycles and also had the highest sound absorption values when the sample thickness was 15 and 25 mm.